Relationship of Environmental Disclosure of Renewable Energy, Carbon Emissions, Waste Management, Water Consumption, and Banks’ Financial Performance - Emmanuel, Yinka Lydia; Doorasamy, Mishelle; Kwarbai, Jerry D.; Otekunrin, Adegbola Olubukola; Osakede, Uche Abamba (International Journal of Energy Economics and Policy, 2024)
In recent years, sustainable banking principles have been employed in the daily operations of deposit money banks in Nigeria. This study examines the relationship between environmental sustainability and the financial performance of 14 deposit money banks listed on the Nigerian Exchange Group. It focuses on the impact of environmental disclosure of renewable energy, carbon emissions, waste management, and water consumption (i.e. proxies for environment sustainability) on the bank’s return on assets (ROA i.e. proxy for financial performance). The research spans an 8-year period from 2013 to 2021, using panel data and multiple regression analysis to analyze the data. The data is collected from the annual reports of the deposit money banks listed on the Nigerian Exchange Group. The research design is ex-post facto, utilizing secondary data collection methods. The findings suggest that there is a positive but insignificant association between environmental sustainability indicators (renewable energy, carbon emissions, waste management, and water consumption) and financial performance (ROA). In conclusion, the study finds no significant relationship between and financial performance (ROA).